Convergence of Administrative Law and Criminal Law in Corruption Prevention for National Strategic Projects - Azis Pangeran, Abdul; Rowi, M. Muchlas (Journal of Scientific Insights, 2026)
National Strategic Projects (NSP) occupy a central position in Indonesian development policy as they serve as instruments for accelerating economic growth and equitable distribution of prosperity. The large budget scale, regulatory complexity, and high pressure for project completion make PSNs vulnerable to corrupt practices. To date, efforts to prevent and address corruption in PSNs have been dominated by a repressive criminal law approach that operates after a violation has occurred. This approach has not been fully effective because it ignores the role of administrative law as an instrument for controlling authority and prevention from the project planning and implementation stages. This article aims to analyze the problematic relationship between administrative law and criminal law in preventing corruption in PSNs and to formulate a proportional and functional convergence model. This research employs normative legal research methods with statutory, conceptual, and analytical-critical approaches. The results of the study indicate overlapping authority, unclear boundaries between administrative and criminal errors, and a tendency to criminalize policy discretion, which has resulted in a decline in bureaucratic courage. This article offers a convergence model that positions administrative law as the vanguard of prevention through strengthened supervision, audits, and administrative corrections, while criminal law is selectively positioned as an instrument of last resort. This model is relevant for encouraging national legal policy reforms that are more preventative, equitable, and oriented toward sustainable improvement of National Strategic Project (PSN) governance.